2021
DOI: 10.18778/1508-2008.24.29
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and its Impact on FDI Inflow: Evidence from the EU Member States

Abstract: The aim of the article is to assess institutional quality in 28 EU Member States and to examine the relationship between the quality of institutions and FDI inward stock as % of GDP. This study is structured as follows. Firstly, we reviewed studies dedicated to the relationship between institutional quality and investment attractiveness. Then, we discussed FDI inflow into the EU countries and selected diagnostic variables that later served as the basis for our research in which we used categories of the Global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Many publications confirm the correlation between the quality of the state and the internationalization opportunities of companies. For example (Dobrowolska et al, 2021) out research in all EU member states. The inflow of foreign direct investment into these countries was positively correlated with the quality of the institutions in a given country, which translated into the investment attractiveness of the host country.…”
Section: Internationalization and The Transformation Of The Capital S...mentioning
confidence: 99%
“…Many publications confirm the correlation between the quality of the state and the internationalization opportunities of companies. For example (Dobrowolska et al, 2021) out research in all EU member states. The inflow of foreign direct investment into these countries was positively correlated with the quality of the institutions in a given country, which translated into the investment attractiveness of the host country.…”
Section: Internationalization and The Transformation Of The Capital S...mentioning
confidence: 99%
“…An efficient and effective institutional system may importantly contribute to boosting the investment attractiveness of countries and impact FDI flows. 49 The cited studies have shown that there is a relationship between the quality of governance, the quality of the institutional system and the investment attractiveness of a country. In this way, it can be pointed out that the business environment organizations can be an important element in this arrangement of economic relations.…”
Section: U M C Smentioning
confidence: 99%